Don’t put off until tomorrow what you can do today. The Importance of Land Release Planning - Taboada Mier, José Carlos (2020)
This article aims to identify the release of land is a problem that can be avoided by the State, through effective project planning, as well as the establishment of the minimum necessary to proceed with the award. We will analyze how project planning is important for the development of different sectors of a country, and then determine how the status of PPP awards and land release is.